Phase 1 Studies to Evaluate the Food Effect and Relative Bioavailability of Tablet and Capsule Formulations of Belumosudil in Healthy Adult Subjects. Issue 7 (2nd March 2022) - Schueller, Olivier; McDermott, John; Evans, Phil; Lohmer, Lauren; Alabanza, Anginelle; Patel, Jeegar
Abstract: Belumosudil is a selective Rho‐associated coiled‐coil containing protein kinase 2 inhibitor. A capsule formulation was used during early clinical development of belumosudil; it was later replaced by a tablet formulation, which mimicked the capsule's release properties and facilitated manufacturing scalability. To assess belumosudil's pharmacokinetics, including potential food effects, and evaluate the relative bioavailability of the 2 formulations, 2 phase 1 clinical trials were conducted. Administration of both belumosudil tablets and capsules with food increased exposure ≈2× as compared to the fasted state and delayed time to maximum concentration by 0.5 hour, indicating a decrease in the rate but increase in the extent of absorption with fed administration. Relative bioavailability was slightly higher when belumosudil was administered as tablets vs capsules, although the difference was not clinically meaningful. Safety and tolerability were generally consistent with the known safety profile of belumosudil. The results of these studies support administration of belumosudil with food.